Mapping of Flood-Prone Area Under the Impact of Tidal Influence in Singkawang City - Senoaji, Arif; Soeryamassoeka, S.B.; Gunarto, Danang (Fakultas Teknik Universitas Tanjungpura, 2024)
Flooding is a recurring seasonal hazard that occurs when water overflows its natural channels and inundates surrounding areas. In the last three years, Singkawang City has experienced frequent flooding that has disrupted community activities, including education and public services, although no casualties have been reported. To reduce flood impacts, comprehensive and integrated flood management is required, beginning with the identification and mapping of flood-prone areas. This study aims to analyze tidal characteristics and assess flood vulnerability in Singkawang City by producing a zoning map of flood-prone areas. The analysis used several parameters, including distance from the coastline, river buffer, land slope, land elevation, and land cover. Flood-prone areas were mapped using Geographic Information Systems (GIS) combined with the weighted overlay method. The results show that 24,048.449 ha (43.947%) of the study area are classified as safe from flooding, while 19,938.498 ha (36.436%) are categorized as not vulnerable. Vulnerable areas cover 9,068.206 ha (16.571%), and very vulnerable areas cover 1,666.860 ha (3.046%).